Association between systemic inflammatory response index and eczema among children and adolescents: a cross-sectional study based on NHANES database - Song, Tianping; Dai, Yueying; Xue, Kaiyuan; Yang, Suqing; Yuan, Rui (Frontiers in Pediatrics, 2025)
BackgroundIn previous studies, the systemic inflammatory response index (SIRI) might be a predictor for chronic inflammation, but the relationship between SIRI and eczema continues to be ambiguous. The objective of the study was to clarify the connection between the level of SIRI and eczema prevalence among children and adolescents.MethodsThe National Health and Nutrition Examination Survey (NHANES) was the database from which we accessed information, comprising participants aged 3–19 years. Furthermore, the investigation of the association between SIRI and eczema was carried out by using logistic regression, and restricted cubic spline models were used to explore nonlinear relationships.ResultsA total of 3,397 subjects, featuring a median age of 11.97 ± 4.87 years, were selected, and 368 (10.83%) were diagnosed with eczema among these participants. Statistically significant differences were observed in the baseline SIRI characteristics for age, race, and BMI quartiles (p < 0.001). In adjusted logistic regression models, the negative association between SIRI and eczema was indicated (OR: 0.83; 95% CI: 0.69–1.00, p < 0.05), suggesting that a one-unit increase in SIRI corresponds to a 17.17% decline in the odds of eczema prevalence. Meanwhile, a nonlinear relationship was revealed by the restricted cubic spline (RCS) between SIRI and eczema prevalence among children and adolescents. The findings of subgroup analysis suggested that there were no significant effects of any covariates on this relationship (all p for interaction > 0.05).ConclusionThe association between SIRI and eczema prevalence in children and adolescents is negative, indicating that elevated SIRI exhibits a protective effect against eczema in children and adolescents, whereas those with low SIRI may require closer monitoring for eczema development.